Assessment of the validity of the dog fee in the Silesian Voivodeship - the authors’ own research - Paweł Mrowiec; Katarzyna Fuchs (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Effective implementation of pro bono tasks by local government units may be carried out only if they obtain the necessary income. One of the types of own revenue of local government units on communal level (LGUs) is the dog ownership fee which generally constitutes a very low share in the total income of the commune. At the same time the enforcement of this fee, due to a large number of personal exemptions, requires disproportionate expenditure in relation to the income earned. The purpose of the paper is to verify the legitimacy of maintaining a fee on owning a dog in the communes of the Silesian Voivodeship in the light of the authors’ own research regarding the year 2016. The conducted research indicated that none of the communes of the Silesian Voivodship achieved the income from dog ownership higher than 0.5% of the total income. The effectiveness of the enforcement of fees on dog ownership was analysed in detail, as well as the percentage comparison of dog fee income with other sources of own income. The paper consists of theoretical and empirical part and presents the essence of financial independence of the commune in the context of imposed taxes and local fees.